Implementasi Sistem Passion Pada Efektivitas Kinerja Pegawai Pada PT. Pegadaian Persero CP. Cikampek - Putri Finanti Ramadhani; Puji Isyanto; Dini Yani (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
PT. Pegadaian (Persero) started in 1746 when the VOC founded Bank Van Leening as a financial organization that offered credit with a gold mortgage system in 1746, PT. Pegadaian (Persero) was born. It was revised to shift from a Job Company to a Public Company in 1969 after which it changed back to a Public Company. In 2012, Pawnshop converted its legal structure to a Limited Liability Company (Persero), in accordance with Government Regulation No. 51 of 2011. Pegadaian has evolved into a business solution for the Indonesian people rather than merely a funding institution. The author discovered an issue with the firm's operations during the internship, specifically the lack of consistency in the upkeep of the passion application carried out by the corporate center such that it disturbed the process of ongoing transaction. In order to ensure that the customer transaction process proceeds without any hiccups, the author proposes that the central firm pay attention to the time and impact that occurs when carrying out the repair process. It is preferable if the maintenance is carried out outside of operation hours.